Logística reversa do óleo residual de fritura para produção de biodiesel do Distrito Municipal de Kampfumo-Cidade de Maputo - Matavel, Nilza Isabel (2015)
Waste frying oil (WFO) is a household waste, which causes a negative impact in social, economic and environmental level, when it is improperly discarded. The alternative of the improper disposal is the recycling, which enables the production of a range of profitable products, where biodiesel is highlighted. The use of WFO as a complementary input in Mozambican biodiesel production system, has the potential to strengthen, complement, and expand the development of this sector. The introduction of WFO, will add the value of the sector, and can benefit the rural electrification projects, reducing vulnerability to gastric diseases, pollution prevention, and reduction of diesel imports. In this context, this paper, present the projection of a reverse logistics network to enable the collection and transport of WFO, to ensure their adequate supply for reuse especially for the production of biodiesel in municipal district KaMpfumo. The links / bonds of the network proposed are the producer of WFO and the logistical facilities to enable the reverse process, the returns centers and pre-treatment centers. The mathematical model proposed, was based on a variant of p-Median problem for facilities location. The resolution method was Mixed Integer Linear Programming, implemented in C/C++, and tested with CPLEX. The model was powered by scenarios that evaluated the hypotheses proposed in the study. The scenarios analysis allow to evaluate the hypothesis proposals, estimating the current situation of the WFO collection, the elevation of this collection through population growth over the next years and through implementation of the legal framework proposed to impulse the biodiesel production. The results of modeling generated the opening of 12 returns centers and one pretreatment center for all scenarios. The results show that the collected volume of ORF is the main factor of varying costs of scenarios, and the operating costs and the transportation costs are those with the highest values in the reverse logistic proposed. This work contributes to the decision-making processes regarding the WFO management, and the diversification of raw material to biodiesel production in these country.